Phase-field modeling of hydro-thermally induced fracture in thermo-poroelastic media - Li, Peidong (2022)
This paper develops a phase-field approach to model hydro-thermally induced crack propagation in thermo-poroelastic media. Both thermal conduction and convection, and the fully thermo-poroelastic coupled effect are taken into consideration in the phase-field model. The fluid content is influenced by the volumetric strain, temperature, and pressure. The heat flux is susceptible to temperature change and fluid flux. The injection fluid pressure and thermal loading trigger the variation of elastic energy, and then drive crack propagation, which is captured by the phase-field variable. A segregated solution scheme and the finite element implementation details are provided here for solving the nonlinear thermo-poroelastic problem. Several examples are tested to verify the present approach and to show its ability to simulate hydro-thermally induced crack propagation in the application of cold fluid injection in a cracked reservoir. The numerical results indicate that the development of the thermal effect on crack propagation is slow when compared with that of the fluid pressure. The present approach can serve as a convenient simulation tool for crack propagation in geothermal and oil/gas reservoir developments.